Reproduksi Stereotip dan Resistensi Orang Katobengke dalam Struktur Masyarakat Buton - Tasrifin Tahara (Antropologi Indonesia, 2012)
Buton manuscripts indicated that Buton Kingdom appeared in 14th Century. In the periods of the 17 th, 18th, and 19th centuries, Buton Kingdom initiated to be the free kingdom. In the begining of 20th , dutch colonial goverment incorporated that the Buton kingdom and placed it under their rule. The principles were laid down based on the social cultural in eceonomic development. Relation to be governed especially are in the field of education, health, and economy. In 1960, Buton kingdom was dissolved following the death of Sultan Laode Muhammad Falihi as the last sultan. During the kingdom era, Buton social system consisted of three groups namelly kaomu, walaka, and papara. The system was established as power of ideology in Buton social political system in the era of goverment the fourth Sultan Dayanu Ikhsanuddin in 1578-1615. The Katobengke people as the subject and object of this paper belong to papara group. In the era of Buton Kingdom, the society was dominated by kaomu and walaka groups. This condition existed until the new order era, where in this period the dominant groups still have cultural and stereotype views toward this people as ini the era Buton kingdom. This paper focuses on the phenomena of power in the dynamic Buton’s social structure. In the Buton social structure, kaomu and walaka groups claimed them selves as the groups who have higher civilization in comparation with the Katobengke people, until today. Key words: Stereotype, Resistance, Social Structure